Comparison of the pharmacokinetics and pharmacodynamics of dapagliflozin in patients with type 1 versus type 2 diabetes mellitus. Issue 3 (8th January 2016) - Tang, W.; Leil, T. A.; Johnsson, E.; Boulton, D. W.; LaCreta, F.
Abstract : Aims: To compare the pharmacokinetics and pharmacodynamics of dapagliflozin in patients with type 1 diabetes mellitus (T1DM) versus type 2 diabetes mellitus (T2DM) in order to explore the potential of dapagliflozin as add‐on therapy to insulin in patients with T1DM. Methods: Steady‐state pharmacokinetics and pharmacodynamics of dapagliflozin (1–100 mg) were evaluated in a meta‐analysis of patients with T1DM or T2DM. A model was constructed of the relationship between dapagliflozin systemic exposure and urinary glucose excretion (UGE) in patients with T1DM versus those with T2DM. Results: Data were analysed from 160 patients (T1DM, n = 70; T2DM, n = 90). Dapagliflozin systemic exposure (maximum concentration and area under the curve) increased similarly in a dose‐related manner in both patient populations. Dose‐dependent increases in 24‐h UGE were observed with dapagliflozin in both populations. Unadjusted results showed that with regard to UGE response, dapagliflozin was more potent in patients with T1DM {mean half‐maximum effective concentration [EC50 ] = 2.72 ng/ml [95% confidence interval (CI) 1.14, 5.08]} than in patients with T2DM [EC50  = 12.2 ng/ml (95% CI 4.91, 21.1)]. After normalization for baseline fasting plasma glucose, estimated glomerular filtration rate and UGE, however, the UGE potency of dapagliflozin was similar between the two populations [T1DM: mean EC50, 8.12 ng/ml (95% CI 2.95, 14.6); T2DM: mean EC50, 7.75 ng/ml (95% CI 1.35, 18.1)]. Conclusions: Dapagliflozin pharmacokinetics and the predicted UGE dose exposure response to dapagliflozin were similar in patients with T1DM and those with T2DM and suggest that the dapagliflozin dosages currently used for the treatment of T2DM may provide benefit as add‐on therapy to insulin in patients with T1DM.